Current status and trends of research on microplastic fugacity characteristics and pollution levels in mangrove wetlands - Bin Chen; Bin Chen (Frontiers in Environmental Science, 2022)
Microplastics have been widely detected in the environment, while mangrove wetlands are considered barriers to land-based plastic transport to the ocean, requiring special attention. However, the current literature is distributed and broad besides limited information on the fate characteristics and pollution levels. This study uses a systematic literature review method to analyze the current research status and future trends. In this study, the literature is summarized and concluded that Characteristics including color, shape, size, polymer chemistry and surface microstructure are the basic information for microplastic research in mangrove wetlands. Size is the key to studying distribution and convergence without international standards. The shape is vital to study its sources and environmental processes. Color affects biological predation and is important information for studying ecological risk. The chemical composition of plastics is the key to studying microplastics’ fingerprint information, source, and sink. The surface microstructure is an important basis for studying adsorption behavior and aging processes. Mangrove microplastic studies in China are mainly on the southern and southeastern coasts, and microplastic pollution is more severe in Fujian, Guangdong, and Guangxi than in Hainan. In contrast, studies on mangrove microplastics abroad are mainly concentrated in Southeast Asia, the Middle East, and South America. Overall, microplastic contamination was detected in the major distribution areas of mangroves worldwide and was correlated with mangrove density and human activities.